Congenital Adrenal Hyperplasia (CAH) - Causes, Diagnosis, Symptoms, Treatment - Targoński, Oskar; Targońska, Marta; Madej, Adrianna; Suława, Adrian; Furgalska, Julia; Fedorowicz, Sebastian; Basiak, Aneta; Ptasiński, Aleksander; Niekurzak, Rafał; Buczek, Agnieszka (Quality in Sport, 2024)
Introduction and Purpose: Congenital adrenal hyperplasia represents a group of genetic disorders characterized by improper adrenal steroidogenesis, resulting in deficiency or absence of cortisol and/or aldosterone, and varying degrees of disturbances in sexual development. The aim of this study is to raise awareness about the disease, enabling early diagnosis and contributing to reducing neonatal mortality, as the first clinical manifestation of CAH can be the life-threatening salt-wasting syndrome. State of Knowledge: Congenital adrenal hyperplasia (CAH), also known as congenital adrenal hyperplasia, encompasses a group of inherited disorders affecting the adrenal glands located above the kidneys. Adrenal glands produce various hormones, including cortisol, aldosterone, and androgens. CAH involves deficiencies in the enzymes necessary for the production of these hormones, leading to hormonal disturbances. Summary: Congenital adrenal hyperplasia (CAH), also referred to as congenital adrenal hyperplasia (CAH), describes a group of genetic diseases causing defects in adrenal hormone synthesis. CAH results in deficiency or absence of cortisol and/or aldosterone. The most common causes are mutations in the CYP21 gene (21-hydroxylase deficiency), CYP11B2 gene (11β-hydroxylase deficiency), and HSD3B2 gene (3β-hydroxysteroid dehydrogenase deficiency). Enzymatic deficiencies lead to compensatory increases in CRH and ACTH secretion, causing adrenal hyperplasia and excessive androgen synthesis.